The use of advanced vs. conventional imaging modalities for the diagnosis of subchondral bone injuries. (21st January 2022) - Lesca, H.; Fairburn, A.; Sherlock, C.; Mair, T.
Summary: Damage to the subchondral bone has been associated with a number of orthopaedic diseases. Diagnostic imaging is, therefore, critical in identifying disease and damage of the subchondral bone, not only for the diagnosis of joint and subchondral bone disease causing lameness, but also for identifying early/pre‐symptomatic damage. The aims of this Critically Appraised Topic (CAT) were to assess the published evidence for the use of advanced imaging techniques (magnetic resonance imaging [MRI] and computed tomography [CT]) in the diagnosis of subchondral bone disease in the distal limb joints (metacarpo/metatarsophalangeal and interphalangeal joints) of the adult horse, and to compare the diagnostic value of these techniques with radiography. In the studies reviewed in this CAT, advanced imaging modalities (MRI and CT) were superior to routine radiography for the diagnosis of subchondral bone injury of the distal limb joints. In a small percentage of horses, post‐MRI reevaluation of the initial radiographs or acquiring further lesion‐orientated radiographs allowed the identification of the subchondral bone injury. Extended radiographic examinations, including non‐standard views, might increase the sensitivity of radiography to detect subchondral bone injuries, however, currently CT and MRI may be considered the "gold standard" imaging modalities. More studies comparing the identification of subchondral bone lesions on imaging and by histopathological/gross examination would be useful to assess more precisely the sensitivity and specificity of the different modalities.